Self-Criticism of the Tabarru' Contract in Islamic Insurance (Fiqh Mu'amalah Perspective) in the Islamic View of Life - Muhamad Said (Penerbit Hellow Pustaka, 2025)
The growth of the Islamic economy in Indonesia has been quite rapid in recent years. This is accompanied by growth in financial institutions, both banking and non-banking. This can be seen in the increasingly innovative contracts, such as the now-popular multi-contracts. To the point that one of the tabarru' contracts, which has the meaning of mutual assistance, exists in Islamic insurance institutions, now feels like a tijaroh contract that spices up the transaction with profit. The purpose of this study is to examine the tabarru' contract carried out by Islamic insurance institutions and critique it through the tabarru' theory approach from the perspective of muamalah fiqh. Using qualitative research methods, using secondary data sources, the researcher attempted to describe the content of the data collection technique using deductive documentation methods. He found that insurance institutions still feel like capitalism labeled as sharia. He also concluded that the institution of zakat, infaq, shodaqoh, and waqf (ZISWAF) can be the best solution for Muslims to truly help each other.